Translanguaging in Action: Shaping Bilingual Communicative Strategies - Aloyan, Zh. L.; Barseghyan, S. S.; Hovhannisyan, N. A.
This study examines the discursive manifestations of translingualism and transculturalism, emphasizing the linguistic specificities of contemporary bilingual environments. The research applies and expands upon S. Gural’s notions of the interdependence of discourse and socio-cultural practice, as well as the context-discourse relationship in modern bilingualism. The bilingual individual operates within a dynamic interaction of linguistic and cultural frameworks, simultaneously shaping and being shaped by discursive and cognitive-communicative processes of both their native and a cquired sociocultures. Այս ուսումնասիրությունը հետազոտում է տրանսլեզվաբանության և տրանսմշակութայնության դիսկուրսիվ դրսևորումները՝ ընդգծելով ժամանակակից երկլեզու միջավայրերի լեզվական առանձնահատկությունները: Այն կիրառում և ընդլայնում է Ս.Գուրալի դիսկուրսի և սոցիալ-մշակութային պրակտիկայի փոխկախվածության, ինչպես նաև համատեքստի և դիսկուրսի միջև փոխհարաբերության վերաբերյալ հասկացությունները ժամանակակից երկլեզվության մեջ: Երկլեզու անհատները գործում են լեզվական և մշակութային շրջանակների դինամիկ փոխազդեցության մեջ՝ միաժամանակ ձևավորելով և ձևավորվելով իրենց բնիկ և ձեռքբերովի սոցիալ-մշակութային դիսկուրսիվ և ճանաչողական-հաղորդակցական գործընթացներով: В этом исследовании рассматриваются дискурсивные проявления транслингвизма и транскультурализма, подчеркивая лингвистические особенности современных двуязычных сред. Исследование применяет и расширяет понятия С.Гураля о взаимозависимости дискурса и с оциокультурной практики, а также об отношениях контекста и дискурса в современном двуязычии. Двуязычный индивид действует в динамическом взаимодействии языковых и культурных рамок, одновременно формируя и формируясь дискурсивными и когнитивно-коммуникативными процессами как своей родной, так и приобретенной социокультуры.
Keywords: Dynamic linguistic environments